Propiedad planta y equipo de la empresa Odorisio, periodo 2022. - Sánchez Iturralde, Rosa Iveth (2023)
The Odorisio company is located in the Los Robles citadel of the City of Babahoyo, it is dedicated to the construction of streets, highways, sidewalks, bridges and other roads for vehicles or pedestrians, in this case study the problems that They appear in the company and it causes inconvenience when providing a service due to the machinery in poor condition and the short rental contract, the problems of property, money and equipment cause concern in the company and that damages the image and credibility of the same. In this case study, an interview was carried out with the Manager of the Company and a SWOT analysis was carried out to obtain information and to be able to identify both internal and external problems of the company. This case study is under the line of research Financial, Administrative, Tax, Audit and Control Management and with the subline Public and Private Companies and Institutions for the reason that the Odorisio dam is a private company, the method used is the evaluative one. of a qualitative nature and the deductive method by which an investigation analysis will be allowed. The results of the interview and the SWOT analysis that was carried out where the strategies were obtained have been obtained, in conclusion we observe that the problems that are found in the company is the lack of maintenance of the machinery is scarce and this causes the little contract of rent, workers are not trained and causes low performance and income and utility of the company without very low, inadequate acquisition of spare parts, warehouses are occupied by another company and causes problems and conflicts between workers.